Clinical impact of quality nursing combined with health education pathway on quality of life and sleep in severe aplastic anemia patients complicated with infection: a randomized clinical trial - Shen, Wei; Wei, Feng (Frontiers in Medicine, 2025)
ObjectiveThis research aimed to elucidate the clinical impact of quality nursing combined with a health education pathway on the quality of life and sleep in patients with severe aplastic anemia (SAA) complicated by infection.MethodsA total of 130 SAA patients complicated with infection, admitted to the Hematology Department of our hospital between February 2022 and February 2024, were selected as research subjects. Using the number table method, participants were randomly divided into an observation group (OG) and a control group (CG), with 65 patients in each group. Patients in the CG received conventional nursing care. In addition to conventional nursing care, those in the OG received quality nursing care combined with health education. The health knowledge awareness rate, quality of sleep, quality of life, inflammatory indicators, immune function indicators, improvement of clinical symptoms, and occurrence of adverse reactions were analyzed and compared.ResultsAfter the intervention, the health knowledge awareness rate was significantly higher among patients in the OG than those in the CG (p = 0.002). The Pittsburgh Sleep Quality Index (PSQI) scores in the OG were significantly lower, while sleep duration was significantly longer compared to the CG (p < 0.0001). Additionally, quality-of-life scores in the OG were significantly higher than those in the CG (p < 0.0001). Patients’ PSQI scores were inversely proportional to their quality-of-life scores in both groups (p = 0.0044, p = 0.0007, p = 0.0003, and p < 0.0001). Conversely, sleep duration was positively correlated with quality-of-life scores in both groups (p = 0.005, p < 0.0001, p = 0.0005, and p < 0.0001). After the intervention, levels of C-reactive protein (CRP), procalcitonin (PCT), and interleukin-6 (IL-6) were significantly lower in the OG than in the CG, while the CD4/CD8 ratio in the OG was significantly higher than that in the CG (p < 0.0001). Additionally, the time to infection control, time for body temperature to return to normal, time for cough disappearance, and time for lung rales disappearance were all significantly shorter in the OG than in the CG (p < 0.0001). The total incidence of adverse reactions in the OG depicted a reduction in comparison to that in the CG (p = 0.013).ConclusionThe combined application of quality nursing and a health education pathway in nursing practices of SAA patients demonstrates significant clinical benefits. It can improve patients’ health knowledge awareness, enhance sleep quality and overall quality of life, enhance immune function, attenuate adverse reactions, and facilitate recovery. This approach is worth promoting further in clinical practice.